Bolivia : Staff Report for the 1999 Article IV Consultation and Request for Second Annual Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2000)
A considerable degree of macroeconomic stability was achieved by Bolivia, and by the steadfast implementation of structural reforms, most of the distortions that adversely affected the economy in the early 1980s were removed. The Bolivian authorities are committed to fighting poverty. Executive Directors urged the authorities to proceed decisively with the envisaged reform of labor regulations in 2000 to enhance external competitiveness, make Bolivia's regulations complaint with the norms of the International Labor Organization, and broaden the coverage of the formal economy.